2004
DOI: 10.1105/tpc.104.023176
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Evolution of the Pyrrolizidine Alkaloid–Mediated Defense System in Separate Angiosperm Lineages w⃞

Abstract: Species of several unrelated families within the angiosperms are able to constitutively produce pyrrolizidine alkaloids as a defense against herbivores. In pyrrolizidine alkaloid (PA) biosynthesis, homospermidine synthase (HSS) catalyzes the first specific step. HSS was recruited during angiosperm evolution from deoxyhypusine synthase (DHS), an enzyme involved in the posttranslational activation of eukaryotic initiation factor 5A. Phylogenetic analysis of 23 cDNA sequences coding for HSS and DHS of various ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 55 publications
2
121
0
1
Order By: Relevance
“…For example, the pyrrolizidine alkaloids are found in such diverse families as the Orchidaceae, Fabaceae, Boraginaceae, and Asteraceae. Analysis of the first biosynthetic step, homospermidine synthase, indicated that this enzyme has been recruited from a primary metabolic enzyme, deoxyhypusine synthase, at least four times over the course of evolution (32). Besides alkaloids, groups such as the cardenolides, a type of glycosylated steroid found in the Liliaceae, Ranunculaceae, Brassicaceae, and Apocynaceae, among other families, have also been proposed to have originated polyphyletically (33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pyrrolizidine alkaloids are found in such diverse families as the Orchidaceae, Fabaceae, Boraginaceae, and Asteraceae. Analysis of the first biosynthetic step, homospermidine synthase, indicated that this enzyme has been recruited from a primary metabolic enzyme, deoxyhypusine synthase, at least four times over the course of evolution (32). Besides alkaloids, groups such as the cardenolides, a type of glycosylated steroid found in the Liliaceae, Ranunculaceae, Brassicaceae, and Apocynaceae, among other families, have also been proposed to have originated polyphyletically (33).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of a complex benzylisoquinoline alkaloid pathway in an ancestor common to the basal angiosperms is in contrast with the proposed independent recruitment of pyrrolizidine alkaloid biosynthetic enzymes in at least four different angiosperm lineages (Reimann et al, 2004). Two scenarios have emerged concerning the relationship between the cell type-specific localization and evolutionary origin of plant alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 10 years, scientists have had fascinating insights into the evolutionary creation of genetic diversity of secondary metabolism. The evolution of new genes by duplicating the genes of primary metabolism, followed by the functional diversification or new functionalization of the duplicates under the selection pressure of the environment (41,42), has been demonstrated for key biosynthetic enzymes of a number of classes of secondary metabolites, such as terpenoids (43), polyketides (44), phenolic esters (45), benzoxazinone alkaloids (46), and pyrrolizidine alkaloids (47). In conclusion, we see that the evolutionary ideas of Stahl and his contemporaries are confirmed by recent concepts of molecular evolution of plant secondary metabolism.…”
Section: Early Chemical Ecology: Why Neglected and Forgotten For Decamentioning
confidence: 99%